Permainan Bom Angka dalam Konsep Kelipatan Persekutuan Terkecil untuk Anak Sekolah Dasar - Adrelia, Dyah Indah; Kurniawati, Venny; Prahmana, Rully Charitas Indra (Jurnal Elemen, 2015)
The purpose of this research is that students are able to understand the basic concepts of Least Common Multiple (LCM) easy by using traditional games in Palembang, namely Bom Angka. The method used is design research with preliminary design, teaching experiment, and retrospective analysis stage, with the subjects were primary school students in the fourth grade. The results of this study indicate that the use of the traditional game in LCM motivated students to be more interested in learning mathematics, because students can learn and play at the same time. In addition, the pronunciation of numbers in sequence once uttered a bomb in every multiple of the numbers that have been agreed enables students to think quickly while helping students memorizing multiplication automatically, who were eventually able to instill the concept of LCM well.Â